Plato against the naturalism: thestaggered dialectic of Cratylus - Spangenberg, Pilar (Revista Archai, 2025)
The purpose of this work is to illuminate the par-ticular refutative dynamics used in Plato’s Cratylus to defend the conventionalist thesis. although Socrates seems to refute two antithetical positions using arguments from one position against the other, the dialogue displays a complex dialectical development that supposes a refutation of, on the one hand, a particular understanding of conventionalism linked with rela-tivism, which is not the one that Socrates accepts in the end. and, on the other hand, regarding naturalism, the dialectical dynamics involves two different moments: the first one brings all the ideas involved or linked in the naturalistic thesis to light; and the second one implies a progressive argumentation against the whole built in the first part of the dialogue, so that the ar-gumentation wouldn’t be a continuum but rather would involve different stages. This particular refutation would explain partial concessions to naturalism that in the end will be flatly rejected